If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -1a = 8t Reorder the terms: -1a + 5t = 8t Solving -1a + 5t = 8t Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5t' to each side of the equation. -1a + 5t + -5t = 8t + -5t Combine like terms: 5t + -5t = 0 -1a + 0 = 8t + -5t -1a = 8t + -5t Combine like terms: 8t + -5t = 3t -1a = 3t Divide each side by '-1'. a = -3t Simplifying a = -3t
| (49/7)+3=100/7 | | (49/7)+3=100/ | | 5(x+9)-2x=18 | | 2y=-7+3 | | 7y+9=4y | | 4(6)+3y=18 | | lnx=-7 | | X^4=8x^2+20 | | 16x+1+25=122 | | b(13b+5)=8 | | x+4-6=2x-6 | | 16x+26=122 | | 8x=9x-5/2 | | x^2=6x+4 | | 3.67+3= | | -4x^2+24x=0 | | (X-3)+x+((x-3)*3)=38 | | 9b-2=-38 | | 15n-4=41 | | 7n+2=9 | | -(1/3)-(2/3)=x | | -3v-3x=15 | | -3v+3x=12 | | 1m+5=25+4 | | -5a+c=-30 | | 101-6x=12x+19 | | ln(8x+5)=ln(5x-1) | | -2/3*i=-3 | | 2y-6z=-12 | | 16x=9x-5 | | 8h^4-26h^2+15=0 | | 4y/3=34 |